PENGELOLAAN LAHAN BERDASARKAN INDEKS BAHAYA EROSI DAN EKONOMISUB DAS PACANGKUDA HULU KOTA PALOPO - Nurhapisah Nurhapisah; Amir Tjoneng; Saida Saida (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2019)
The main problem of damage to land resources in the Pacangkuda Hulu watershed is caused by erosion. Conversion of forest areas into cultivation areas and land management that does not apply the right soil conservation techniques is the cause. The purpose of this study was to determine the extent of erosion, tolerated erosion (TSL), erosion hazard index (IBE), land management patterns and farming income in the Upper Pacangkuda watershed. This study uses a survey method of USLE method erosion prediction analysis. The results showed that the highest erosion was in shrub land use, which amounted to 696.424 tons / ha / year, while the lowest erosion was found in primary forest land use which was 2,350 tons / ha / year. The highest tolerated erosion was found in mixed plantation land use of 29.758 tons / ha / yr and the lowest was in shrub land use of 10.588 tons / ha / year. The highest erosion hazard index is found in shrub land use of 65.788 tons / ha / year with very high IBE criteria while the lowest erosion hazard index is secondary forest land use of 0.107 tons / ha / year with low IBE criteria. Land management and agrotechnology which are alternatives are Multiple cropping agriculturesystems with gulud and bangku terrace conservation actions. Income from farming based on Sayogyo is still categorized as poor to very poor with income ranging from Rp. 9,074,076, / up to Rp. 12,799,764 / year / year. Compared with income based on Palopo City of Rp. 2,200,000, the farming income is still relatively low